How Transformational Leadership and Organizational Learning Impact Organizational Citizenship Behavior: A Meta-Analysis - Usep Kasman; Merry Lapasau; Oom Rohmah; Bambang Sumadyo (Postgraduate, University of Mataram, 2025)
Organizational Citizenship Behavior (OCB) plays a crucial role in enhancing school effectiveness, yet research on how transformational leadership and organizational learning influence teachers’ OCB has produced mixed results. To address this gap, this study conducted a quantitative meta-analysis to integrate empirical evidence and measure the strength of these relationships. A total of 35 studies published between 2020 and 2025 were systematically collected from Scopus, SINTA, and Google Scholar and analyzed using JASP 0.14.1 with a random-effects model and correlation effect size (r). The analysis revealed that transformational leadership demonstrated a stronger positive association with teachers’ OCB (r = 0.515, p < 0.01) compared to organizational learning (r = 0.387, p < 0.01). Tests of heterogeneity indicated a moderate level of variation across studies, and no signs of publication bias were detected. These results highlight the critical need to foster transformational leadership and nurture a culture of learning in schools as strategic efforts to promote OCB among teachers.